Necrotizing Streptococcus pyogenes Infiltrating Conjunctiva and Tenon's Capsule: A Case Report - de Freitas Santoro, Dalton (Case Rep Ophthalmol, 2021)
We report a case of a patient with necrotizing infection of the conjunctiva and Tenon's capsule caused by Streptococcus pyogenes, a rare and atypical ophthalmologic condition. A 50-years-old male patient with acute red-eye, purulent discharge, and pain diagnosed with post-septal cellulitis presented with a yellowish and dense membrane covering the ocular surface with necrotic Tenon's capsule. Patient was hospitalized, and intravenous antibiotics were initiated (ceftriaxone and clindamycin). Topical antibiotics and corticosteroids were also administered, and the infection was eradicated in 2 weeks. Ancillary exams excluded rheumatologic involvement. Conjunctival culture confirmed Streptococcus pyogenes growth. Tenon's biopsy revealed unspecific acute inflammatory necrosis. This is an uncommon condition in daily ophthalmological clinic. Literature review reported 3 cases associated with previous ocular surgery.